181 Harnessing staff values to catalyse workplace change. (16th November 2020) - Audhali, Nadia; Moore, Anna; Martin, Tim; Munro, Charlotte; Wedmore, Florence
Abstract : Green@Bart's is a 60 strong multidisciplinary staff special interest group at one the UK's largest Acute Foundation Trusts. All working on a voluntary basis and united by a passion for sustainability and climate action. Despite the WHO stating climate change as the most significant Public Health issue of our generation, reducing carbon emissions from healthcare remains a huge challenge, and ever-bolder legal targets eg 'Net Zero' emissions by 2050, require innovative thinking and support at every level to succeed. Guided by our passion for addressing these issues Green@Barts had the courage to approach senior leadership through Board meeting thereby winning Chief Executive support and valuable networking opportunities to enable our work. Within one year of its inception Green@Barts are now invited by Trust leaders for our input. We are currently consulting on post-Covid transformational work for Trust-wide outpatients and emergency department. We have shared best practice with staff at other Trusts, supporting them to set up their own sustainability staff group, and there are plans for a mini-conference. We see the necessity of winning hearts and minds and education and awareness raising for staff and patients run throughout our work. Other work ranges from providing scrutiny and comments on the Trust's key sustainability and emission reduction document- the SDMP aka The Green Plan, as well as the Architect Tender document for Whipps Cross redevelopment, thereby securing an aspiration for the UK's first 'Carbon Net Zero' hospital. Secondary beneficial outcomes include promoting staff engagement and belonging, both key for promoting resilience and reducing burnout. Connecting through shared values can powerfully support a change agenda, and this can be driven by highly motivated staff with the courage to speak up. This bottom up approach complements the top down work from Trust leadership, vital to achieving maximum results.